2003
DOI: 10.1385/jmn:20:3:349
|View full text |Cite
|
Sign up to set email alerts
|

M<sub>1</sub> Muscarinic Agonists Can Modulate Some of the Hallmarks in Alzheimer's Disease: Implications in Future Therapy

Abstract: M1 muscarinic receptors (M1 mAChRs) play a role in an apparent linkage of three major hallmarks of Alzheimer's disease (AD): beta-amyloid (Abeta) peptide; tau hyperphosphorylation and paired helical filaments (PHFs); and loss of cholinergic function conducive to cognitive impairments. We evaluated the M1 muscarinic agonists AF102B (Cevimeline, EVOXAC trade mark : prescribed for Sjøgren's syndrome), AF150(S), and AF267B on some of these hallmarks of AD. Activation of M1 mAChRs with these agonists leads, inter a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
84
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 147 publications
(86 citation statements)
references
References 24 publications
2
84
0
Order By: Relevance
“…Furthermore, M 1 receptors appear to be a useful target for AD therapy (Bodick et al, 1997;Fisher et al, 2003). Because sympathetic ingrowth impacts M 1 receptor function, and it has been found in hippocampus of some AD patients (Booze et al, 1993), a better understanding of the cellular mechanisms that both encourage and inhibit sprouting, as well as how synaptic function is modulated as a result, could have significant clinical impact for neurodegenerative diseases involving the cholinergic system.…”
Section: Altered M 1 Signaling After Cholinergic Denervation and Ingrmentioning
confidence: 99%
“…Furthermore, M 1 receptors appear to be a useful target for AD therapy (Bodick et al, 1997;Fisher et al, 2003). Because sympathetic ingrowth impacts M 1 receptor function, and it has been found in hippocampus of some AD patients (Booze et al, 1993), a better understanding of the cellular mechanisms that both encourage and inhibit sprouting, as well as how synaptic function is modulated as a result, could have significant clinical impact for neurodegenerative diseases involving the cholinergic system.…”
Section: Altered M 1 Signaling After Cholinergic Denervation and Ingrmentioning
confidence: 99%
“…It has been hypothesized that the M 1 subtype could be a promising target for the design and development of drugs that improve cognitive abilities [2]. It was suggested that M 1 muscarinic agonists might offer an advantage in treating the AlzheimerÕs disease, by activating post-synaptic M 1 receptors [2][3][4][5]. This strategy is presumably less limited than using acetylcholinesterase inhibitors, because it does not require the production and release of acetylcholine from presynaptic terminals.…”
Section: Introductionmentioning
confidence: 99%
“…The members of the muscarinic acetylcholine receptor family are prominent among the GPCR subtypes associated with cognitive function because lesions in cholinergic innervations to the hippocampus and other brain areas are widely thought to underlie the cognitive deficit observed in Alzheimer's disease (5). Whereas the M 1 -muscarinic receptor subtype has been proposed to be the subtype associated with acetylcholine-mediated cognition (6,7), recent gene-knockout experiments have cast doubt on the direct role of this receptor subtype in learning and memory (1,8). This has been reinforced by the discovery of a novel selective M 1 -muscarinic receptor antagonist that was effective in blocking M 1 -muscarinic receptor-mediated seizures in vivo but had no effect on hippocampal-based contextual fear conditioning (9).…”
mentioning
confidence: 99%